The Macroeconomic Determinants of Credit Risk in Syrian Private Traditional Banks -Econometric Study- (Journal of Hama University, 2021)
This study aims to identify the macroeconomic determinants that effects on the credit risk of the traditional private banks operating in Syria in the period between 2011-2019. Each of the following macro variables was tested: GDP, inflation rate, unemployment rate, final consumer spending, effective real exchange rate. Using quarterly data, the ARDL methodology was applied to test co-integration. The results showed that there is a negative impact of GDP on credit risk, while the effect of inflation and final consumer spending was positive on credit risk, however no effect of the effective real exchange rate and unemployment rate on credit risk was observed during the studied period. These results were consistent in the long and short term. It is mentioned that due to insufficient statistical data for some economic variables, the study was unable to test the effect of all variables that could affect credit risk, and this is one of the limits of the study.